The discovery and characterisation of novel antimicrobial peptides against bacterial pathogens with porcine host specificity. - Clarke, Britany (2023)
Natural antimicrobial peptides (AMPs) are crucial host defense peptides with multifactorial biological activity and AMPs reinforce the first-line innate immune response to safeguard hosts from invading microbes and viruses. Focal aims of this study concerned constructing a discovery pipeline to identify novel AMPs against bacterial pathogens with porcine host specificity. Outlined herein the AMP discovery pipeline was structured to screen large and diverse peptide libraries via two parallel screening approaches; i) Screening libraries ≥109 in size via phage display technology (pIII system, 3+3) to identify enriched binder ligands. Alternatively, explored was the exploitation of ii) an Escherichia coli recombinant peptide expression soft agar-based assay; for direct antimicrobial characterisation of peptide sub-libraries 106 to 107 in size. E. coli JE5505 (F− 1po his proA argE thi gal lac xyl mtl tsx) is a lipoprotein Δlpp-254 mutant and the overlay centres on recombinant peptides leaking from the periplasm into surrounding media generating visible zones of inhibition around colonies. A 0.7% Mueller-Hinton E. coli JE5505 soft agar overlay assay was optimised for both the scanning of known AMPs and screening randomised peptide library. The Mueller-Hinton leaky E. coli JE5505 overlay assay approach offered high-throughput (≤ 104 library colonies per assay) and cost-effective screening. However, the overlays were incompatible with screening randomised libraries as no antimicrobial activity was observed when screening AMPs which were not class-II bacteriocin Plantaricin-423 (Pln-423) or respective improved Pln-423 mutants obtained from literature. Screening methods were optimised alongside designing a degenerate primer strategy to bias amino acid distribution in a manner which increased the prevalence of peptide library candidates with antibacterial phenotypes. A training dataset of 187 natural AMPs against pig bacterial pathogens were collected from the ADP3 database and used as the baseline for amino acid distribution analysis (APD3_ AMP_PigPathogenDataset). The degenerate primer strategies utilised to construct two 16 mer-peptide phage libraries herein were; i) the NNK randomisation scheme; “N”: A/T/G/C and “K”: G/T, a highly exploited conventional peptide degenerate mutagenesis strategy. Compared to ii) the VNN15+(TTT)1 randomisation, “V” = A/G/C, and “TTT” reintroduces VNN scheme excluded phenylalanine residue in one out of sixteen peptide region amino acid residues. VNN15+(TTT)1 randomisation “AMP-biased approach” was designed with the rationale of biasing the amino acid distribution towards that observed in the APD3_ AMP_PigPathogenDataset. Whole-construct inverse PCR was exploited for library construction wherein degenerate primers introduced the VNN15+(TTT)1 or NNK randomised peptide region diversity into pSD3 phagemids. Additionally, with ease peptide phage libraries were SpeI digested into sub-libraries (absent of phage -gIII) for screening in the 0.7% Mueller-Hinton E. coli JE5505 soft agar overlay assay. Three categorised AMP amino acids groupings were outlined herein; (a) hydrophobic, (b) basic (cationic), (c) acidic (anionic), or neutrally charged and/or hydrophilic and/or stop codons. Ion Torrent Next Generation Sequencing (NGS) analysis quality control suggested VNN15+(TTT)1 surpassed NNK equivalent libraries, and more closely resembled the overall AMP amino acid groupings of the APD3_ AMP_PigPathogenDataset. A whole-cell phage display approach was then used to screen the VNN15+(TTT)1 and NNK phage propagations against bacterial pathogens with porcine host specificity; Streptococcus suis P1/7 and Salmonella enterica subsp. enterica serovar Typhimurium 4/74. The panning strategy entailed three rounds, and in the final panning step all round two output phage were screened against both test species generating 8 panning datasets with 10 replicates. Round three panning outputs were rescued and then sequenced via Ion Torrent NGS to elucidate >106 library sequences and identify enriched peptide ligands against bacteria targets. TopN and Z score bioinformatic analysis were utilised (Z score: ≥2 or Top50 frequency analysis) and peptides were shortlisted on the presence across ten panning sample replicates, with positive dataset reproducibility of ≥90%, 9/10 panning replicates preferred. Eighty-five peptides were crude synthesised (C-terminal amidation), with the majority being derived from VNN15(TTT)1 library. As in most panning conditions VNN15(TTT)1 library scheme generated a greater number of enriched binders against panning test species. Unfortunately, in vitro microdilution minimum inhibitory concentration (MIC) assays screening revealed <6% of shortlisted candidates demonstrated inhibitory antimicrobial activity against bacteria pig pathogen strains; S. suis P1/7, S. Typhimurium 4/74 or E. coli P433. Antimicrobial peptides identified were weakly active 50 - 200 µM and the most potent AMPs herein were NNK derived. This unfortunately countered the inference of superiority gained from NGS analysis of the VNN15(TTT)1 amino acid distribution and enriched panning ligand pools. Nonetheless, VNN15(TTT)1 phage display derived peptides; Pep_VNN/43 (MIC =100µM) and Pep_VNN/55 (MIC = >100µM) represent novelty in two-aspects; (i) novel application of the degenerate VNN scheme to identify phage display peptide ligands with antibacterial phenotype, and ii) both peptides inhibit S. suis P1/7 in vitro. Pep_NNK/23 additionally inhibited S. suis PI/7, and in both instance the discovery of VNN15+(TTT)1 and NNK phage display derived peptides extends the current knowledge of novel AMP sequences against S. suis. Enriched peptides panned against both S. Typhimurium 4/74 and S. suis P1/7 were able to demonstrate more potent MICs against non-panned test species; E. coli P433. For example, broad-spectrum inhibiting Pep_NNK/17 and E. coli P433 biased Pep_NNK/21 demonstrated the most potent inhibitory activity (MIC = 50µM). Pep_NNK/21 was unable to demonstrate antibacterial activity against the two panning species at 200µM and 800µM, x4 and x16 MIC of E. coli P433. Essentially, both Pep_NNK/17 and NNK/21 further demonstrates that in some instances; phage display technologies likely select for peptide ligands with weak antibacterial action but sufficient binding affinity to be enriched against the test species panned. Pep_VNN/43, Pep_NNK/17 and Pep_NNK/21 exemplify novel antimicrobial peptides with activity against key bacterial pathogens with porcine host specificity. Pig livestock production is highly reliant on the use of antimicrobials to control and prevent the dissemination of disease. S. typhimurium, S. suis and E. coli are amongst the most prevalent bacterial pathogens associated with economically impactful porcine diseases and certain strains can be multidrug resistant. Antimicrobial resistance continues to challenge both animal and human health prospects, and the ever-increasing exhaustion of treatment options is ominously encroaching further towards last-resort antibiotics. Consequently, novel antimicrobial therapeutics with divergent antibacterial mechanisms of action, membrane or intracellular biological targets are required to supplant antibiotic reliance. Presently, AMPs are an underutilised class of antimicrobials however, due to their therapeutic potential AMPs are increasingly garnering the spotlight for substituting antibiotics.